Acknowledging extraordinary women in the history of medical entomology - Troyo Rodríguez, Adriana (2022)
Throughout history, women have been actively involved in the advancement of science, while struggling to overcome challenges to participate and a lack of recognition. Prior to 1950, most women were not included in the lists of “classical” descriptions of iconic scientific figures nor included in the most relevant historical accounts. Since the second half of the twentieth century, great efforts have been made to recognize the contributions of women to the advancement of science, especially since formal scientific careers have been dominated by men, with limited (or no) access to women. Despite these challenging social, political, and cultural contexts, many women have succeeded in making significant advancements, and their contributions are now being acknowledged. Such efforts have led to the publication of recent reviews and compilations on outstanding women in biological sciences. The field of medical entomology is inherently interdisciplinary, focusing on insects and other arthropods that affect human health, with input primarily from the biological and medical sciences and a strong public health perspective. Several reviews and book chapters describing the history of medical entomology have been published over the decades, but few women are mentioned in these publications, even though many women have contributed to this field. Much of the information on these women is currently scattered throughout the published literature and historical records on a wide range of topics, including activism, virology, vector control, and even acarology. Considering that there is no single available compilation of women contributors in the history of medical entomology, this review aims to provide a list of 22 women and their contributions to this field. The list includes women from diverse backgrounds, born in the late 1800s and before 1950, who directly impacted medical entomology in various ways and in different regions of the world. This compilation is far from exhaustive, but it aims to identify role models and examples of extraordinary women to motivate the evolving future of this field.